Correction: Prey selection along a predators' body size gradient evidences the role of different trait-based mechanisms in food web organization. - Esteban Ortiz; Rodrigo Ramos-Jiliberto; Matías Arim (PLoS ONE)
[This corrects the article DOI: 10.1371/journal.pone.0292374.].